Automated health monitoring system - Tanvir Fahim, Sheikh Farhan; Hasan Rudra, S.M. Mahmudul; Roy, Nirvik Guha; Al-Maruf, Abdullah; A-Zannat, Zahrun (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.